Prevention of Violence in Education Through Socio-pedagogical Recommendations Based on the Perceived Level of Risk. - Anastasovski, Ivan; Frichand, Ana; Popovski, L. (Faculty of Physical Education, Sport and Health, University "Ss. Cyril and Methodius", Skopje, 2020)
This research aims to establish socio-pedagogical recommendations for the prevention of violent behavior in education by assessing the perceived level of risk. The level of risk was assessed using a priori constructed questionnaire using the Google forms tool, that was afterwards distributed via e-mail and Facebook to the various respondents involved in the educational process. The group of 101 respondent (62 males and 39 females) is consisted of students, teachers, professors, athletes and sports workers. For the purpose of the research, a set of socio-pedagogical recommendations for prevention of violence in education, were created. Based on the obtained results, the authors propose several specific socio-pedagogical recommendations that are presented in the conclusions at the end of the paper.
Keywords: Socio-pedagogical Recommendations, Violence, Education, Risk level